Proses Produksi Karya Tari Virtual “Nafas Nusantara” - Mega Lestari Silalahi; Denny Eko Wibowo (TAMUMATRA, 2023)
The dance work "Nafas Nusantara" is a new dance creation that departs from the motion of representing four regions, Java, Malay, Bali, and Borneo. Nafas Nusantara is a form of virtual performance work produced as an opening ceremony in the virtual INTERNATIONAL MULTIDISCIPLINARY RESEARCH CONFERENCE ON EDUCATION, SCIENCES AND ARTS (IMReCESA 2021) held in the Philippines. Nafas Nusantara dance works through different stages of production from dance works are live show, the production of Nafas Nusantara works through the stages: pra-production, production, and post-production, where pre-production consists of 4 stages of preparation such as: Drafting the work concept, compiling a production schedule, making storyboards, and forming a production team. Production stage with the process of forming dance and music accompaniment, documenting dance works with cinematographic techniques. The last post-production is the editing and mastering process.